Global spillovers of a Chinese growth slowdown - Shaghil Ahmed; Ricardo Correa; Daniel Dias; Nils Gornemann; Jasper Hoek; Anil Jain; Edith Liu; Anna Wong (Journal of Risk and Financial Management, 2022)
This paper analyzes the potential spillovers of a slowdown in Chinese growth to the United States and the rest of the world. Through a combination of structural VAR and DSGE analyses, we find that (1) spillovers from China to the rest of the world have grown significantly in the past decade; (2) the negative growth spillovers to the United States are more modest than to emerging market economies-particularly for commodity exporters-or other advanced economies, primarily because the latter group has larger direct exposure in trade to China; and (3) although the United States has limited direct financial exposure to China, the negative spillovers to the U.S. economy are amplified significantly if the negative Chinese growth shock leads to adverse global risk sentiment and monetary policy in the United States is constrained in its reaction.
Keywords: F30; G28; E60; 650; China; growth; financial system; spillovers